Primary Mucosa-Associated Lymphoid Tissue (MALT) Lymphoma of the Prostate: MRI and FDG-PET Imaging Findings - Hama, Yukihiro (International Journal of Radiology and Imaging, 2023)
Background: Primary mucosa-associated lymphoid tissue (MALT) lymphoma of the prostate is a rare condition, and there is no report on magnetic resonance imaging (MRI) and its relationship with fluorine-18 fluorodeoxyglucose positron emission tomography (FDG-PET). Objectives: The purpose of this article is to present the MRI and FDG-PET imaging findings of primary MALT lymphoma of the prostate and discuss the imaging findings’ importance in the diagnosis and management. Case summaries: A 73-year-old male patient underwent a prostate biopsy for lower urinary tract symptoms and an elevated serum prostate-specific antigen level. Histopathologic and immunohistochemical findings were consistent with MALT lymphoma. As the tumor was confined to the prostate and adjacent tissues and no lymph node metastases were detected on PET-CT, the diagnosis was primary MALT lymphoma of the prostate. The tumor of the transitional zone infiltrated along the obturator internus muscle and into the pubic bone, the levator ani muscle was almost intact on MRI. Conclusion: The absence of lymph node metastasis or gross muscle destruction but a high degree of invasiveness into surrounding tissues is an important imaging finding in the diagnosis of primary MALT lymphoma of the prostate. Keywords: Differential Diagnosis; MRI; Prostate Neoplasms